Wakacjuszka - Mierzynska, Zofia (Chicago : Z & L Song & Pub. Co., 1983)
Autobiography of the Polish author.
Keywords: Mierzynska, Zofia; Authors, Polish -- 20th century -- Biography; Foreign workers, Polish -- United States; Polish people -- United States -- Biography